(untitled) (International Journal of Engineering and Computer Science, 2017)
The increase in use of automated fingerprint recognition puts on it a challenge of processing a diverse range of fingerprints. To make it supportive in consisting fingerprint detail extraction, quality control is required, which is used in identification/verification. Fingerprint verification is one of the most reliable personal identification methods and it plays a very important role in forensic applications like criminal investigations, terrorist identification and National security issues. Some fingerprint identification algorithm (such as using Fast Fourier Transform (FFT), Minutiae Extraction) may require so much computation as to be impractical. Because quality of fingerprints varies according to the user population’s ages and fingerprint quality has an impact on overall system performance, it is important to understand the significance of fingerprint samples from different age groups.